Analyses of MPPT algorithms in real test conditions - Guimarães, Thiago Fialho (2022)
Maximum Power Point Tracking (MPPT) algorithms are of major importance for optimized yield in gridconnected PV systems. Many algorithms have been investigated. However, most of the works compare these algorithms based on a literature review or on simulation. This paper presents an experimental analysis of MPPT techniques: two of the simplest (Perturb & Observe and Incremental Conductance) and two of the most complex (Fuzzy Logic Controller and Particle Swarm Optimization). The results are carried out in real test conditions, with and without shadow. The power converter is based on a boost converter and a voltage source inverter. The control is implemented using Simulink® and dSPACE 1103 real-time controller board. Moreover, the MPPT techniques of three commercial string inverters are also analysed.